Additive Manufacturing of ceramic components by Digital Light Processing: A comparison between the "bottom-up" and the "top-down" approaches. Issue 6 (June 2019) - Santoliquido, Oscar; Colombo, Paolo; Ortona, Alberto
Abstract: A systematic study of the additive manufacturing of complex ceramic objects was carried out using two different Digital Light Processing (DLP) approaches, the "bottom-up" and "top-down" ones, employing the same projector as light source and a photosensitive Al2 O3 -based ceramic slurry. Cylindrical periodic architectures having different macro-porosity, as well a bulk (dense) component in the form of a disk, were designed and additively manufactured with the two printers employing similar printing conditions. In the "bottom-up" approach, the periodic detachment of the part being manufactured from the bottom surface of the vat, to enable the insertion of a fresh layer of slurry, introduced stresses and deformations in the component, leading to several problems. In the "top-down" approach, the main issue is that the thickness of the printed slices is not precise and constant, due to the difficulty of the viscous slurry to uniformly wet and coat the already printed layers.